EVALUASI PENGGUNAAN OBAT PADA PASIEN DISPEPSIA DI RUMAH SAKIT SWASTA DI PURWOKERTO - Ardhana, I Putu Primanda Dodi; Kurniasih, Khamdiyah Indah; Fauziah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Dyspepsia is a gastrointestinal disorder that affects the stomach. In the event that the pharmaceutical agents employed for the treatment of dyspepsia are not selected in a rational manner, there is a potential for therapeutic failure, the emergence of more serious health complications, the manifestation of adverse drug reactions, and the unnecessary utilization of pharmaceuticals. The objective of this study was to assess the rationality of drug use for dyspepsia patients at a hospital in Purwokerto, specifically focusing on the appropriateness of the selected drug, dosage, and indication. This research is descriptive and employs a retrospective approach. A total sampling technique was employed, yielding a total sample of 71 medical records from the period between January and February 2024. The data collection was conducted in April 2024. The instruments utilized in this study were observation sheets and medical records. The results of this study indicate that the use of drugs for dyspepsia patients at a private hospital in Purwokerto is, in fact, rational. Specifically, the drugs used were deemed to be the appropriate medication 98.6% of the time, the dosage was deemed to be appropriate 100% of the time, and the indication for use was deemed to be appropriate 100% of the time. Therefore, it can be concluded that the use of drugs in dyspepsia patients in private hospitals in Purwokerto is, in fact, rational.